2007
DOI: 10.1186/1471-2393-7-20
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate criteria for identification of near-miss maternal morbidity in tertiary care facilities: A cross sectional study

Abstract: BackgroundThe study of severe maternal morbidity survivors (near miss) may be an alternative or a complement to the study of maternal death events as a health care indicator. However, there is still controversy regarding the criteria for identification of near-miss maternal morbidity. This study aimed to characterize the near miss maternal morbidity according to different sets of criteria.MethodsA descriptive study in a tertiary center including 2,929 women who delivered there between July 2003 and June 2004. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
107
4
18

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(136 citation statements)
references
References 18 publications
7
107
4
18
Order By: Relevance
“…This concept was defined by the World Health Organization (WHO) as ''a woman who, being close to death, survives a complication that occurred during pregnancy, delivery or up to 42 days after the end of her pregnancy'' [8,9]. Maternal near-miss (MNM) cases occur more often than maternal deaths and may give more information because the woman herself can be a source of data [10]. MNM cases have similar pathways as maternal deaths, with the advantages of offering a larger number of cases for analysis, greater acceptability of individuals and institutions since death did not occur [11].…”
Section: Introductionmentioning
confidence: 99%
“…This concept was defined by the World Health Organization (WHO) as ''a woman who, being close to death, survives a complication that occurred during pregnancy, delivery or up to 42 days after the end of her pregnancy'' [8,9]. Maternal near-miss (MNM) cases occur more often than maternal deaths and may give more information because the woman herself can be a source of data [10]. MNM cases have similar pathways as maternal deaths, with the advantages of offering a larger number of cases for analysis, greater acceptability of individuals and institutions since death did not occur [11].…”
Section: Introductionmentioning
confidence: 99%
“…17 It is important to note that in this proxy population-based prospective study, the causes of severe maternal morbidity were very similar to those obtained in the previously described institutional study. 10 This is relevant as it indicates that it is possible to identify interventions that could be carried out during antenatal care 19,20 or delivery 20 to try to reduce the risk of maternal death from specific, identified problems.…”
Section: Definitionsmentioning
confidence: 99%
“…With respect to surveillance of severe maternal morbidity, we found that a two-tiered strategy of surveillance (screening and confirmation) would be more consistent and possibly more effective. 10 As a result of these findings, we tested the application of the severe maternal morbidity scoring system in this same group of women. The severe maternal morbidity scoring system is based on the existence of a continuum of morbidity, with normal pregnancy at one end, passing through the occurrence of a complication and different degrees of severity with maternal death at the other end.…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It represents conditions of extreme gravity or near death (2) . The classification criteria of Severe Maternal Morbidity were standardized by the World Health Organization in 2011 (3) ; previous studies showed significant variation in the estimates of the event (4)(5) . It is estimated that up to 20 cases of severe morbidity occur for each registered maternal death and up to a quarter of the women can suffer severe and permanent sequelae (6) .…”
Section: Introductionmentioning
confidence: 99%